Measuring the Relationship between Urban Environment and Wellness of Residents - Agrawal, Adarsh; Borikar, Paurnima (Calibrating Urban Livability in the Global South, 2024)
This paper analyzes the intricate relationship between the urban environment and resident wellness of a neighborhood in Bhopal, India. The study employed a mixed methods approach, including an expert opinion survey, structured interviews with area representatives, and a user survey of residents of Arera Colony. Both primary and secondary data sources are leveraged to illustrate the impact of the built environment on residents' wellness. Primary data was collected through surveys assessing 70 residents' wellness and interviews with 20 area representatives through a comprehensive literature review, the study identified 13 parameters such as housing, healthcare access, transportation infrastructure, community resources, green spaces, air and noise quality, safety and security, and incorporation of healthy urban design principles. Barriers faced by residents in accessing the services and resources that impact resident’s wellness were identified. The findings indicate that the case area faces emerging concerns regarding rapid commercialization and increased congestion in the area. This study delivers valuable insights into the relationship between the urban environment and the wellness of residents. The findings can help in urban planning and policy decisions to create a healthier, more livable community in this neighborhood and similar contexts.